PENGARUH PEMBERIAN KOMPOS LIMBAH TANAMAN JAGUNG TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Hafiz, Adhanul; Nurhidayah, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2020)
The research aims to determine the effect of giving corn plant waste compost and get the best dose to the growth of cocoa seedling. This research has been conducted in the experimental garden of Agriculture Faculty University of Riau from April until July 2018. The research was conducted experimentally by using Completely Randomized Design (CRD), with six treatments and four replications. Treatments has given consist of corn plant waste compost with dose of 0 g, 25 g, 50 g, 75 g, 100 g and 125 g per 5 kg soil. Parameter observed were increasing of seedling height, stem circumference, number of leaves, leaf blade length, leaf blade width, crown dry weight, root dry weight and ratio of canopy and root. The data obtained were analyzed statistically using analysis of variance with Duncans New Multiple Range Test (DNMRT) at 5 %. Giving corn plant waste compost with dose 125 g per 5 kg soil is the better choice to improve the increasing of seedling height, stem circumference, number of leaves, leaf blade length, leaf blade width, crown dry weight, root dry weight and ratio of canopy and root.Â Keywords: Growth, cocoa seedlings and corn plant waste compost